The Nexus between Financial Inclusion and Monetary Policy: The Case Study of Selected ASEAN Countries - Messayu Dara Komala; Wahyu Widodo (Journal of Economics, Business, and Accountancy Ventura, 2022)
This study examines the relationship between financial inclusion and monetary policy in nine selected ASEAN (Association of Southeast Asian Nations) countries during 2010-2019. To answer the objective of this study, the Vector Error Correction Model (VECM) is used to analyze the effect of financial inclusion on inflation as a proxy of monetary policy effectiveness. In addition, the causality between financial inclusion and monetary policy is also examined in this study. The data used are panels data and collected through secondary sources. The multidimensional approach of IFI (index of financial inclusion) is constructed to represent a comprehensive financial inclusion measurement. The results showed that financial inclusion had a negative effect on inflation in the long-term and short-term; it indicates that an increase in financial inclusion will lower inflation which eventually increases the effectiveness of monetary policy in Indonesia, Malaysia, Thailand, Philippines, Singapore, Vietnam, Cambodia, Myanmar, and Laos. Moreover, a causality exists between financial inclusion indicators and monetary policy in selected ASEAN countries. This study concludes that financial inclusion through access and usage of financial services improves the efficiency of monetary policy in nine selected ASEAN countries in controlling inflation. This study suggests that monetary authorities must emphasize the link between financial inclusion and monetary policy objectives. Advanced financial inclusion can help policymakers formulate and implement monetary policies contributing to economic stability and sustainable growth.